COMPARATIVE ANALYSIS OF EXPERIENTIAL MARKETING AND SOCIAL ENVIRONMENT BETWEEN SINGLE AND MARRIED CUSTOMER OF JOHNNY ANDREAN SALON MANADO TOWN SQUARE - Montong, Marini .; Pangemanan, Sifrid S; Tumewu, Ferdinand . (Universitas Sam Ratulangi, 2017)
Abstract: There is an increasing competition among the beauty salons in Manado Town Square. As one of the salons, Johnny Andrean Salon is forced to keep its customer. Customer revisit intention is a very important part of a business. Experiential marketing and social environment play a part in building customer revisit intention. In order for Johnny Andrean Salon to be able to keep its customer, this study aims to analyze whether there is a significant difference between its single customer and married customer. The result shows that there is a significant difference in experiential marketing, while not in social environment. However, according to the result based on the indicators show that, there are actually two indicators in each category that has a significant difference. In experiential marketing, they are the feel indicator and the act indicator; and social comfort indicator as well employee job enthusiasm indicator for the social environment. Hence, this research proposes that the focus of the improvement in order to develop a better strategy approach to boost the customer revisit intention should be prioritized mostly in these 4 indicators, particularly aimed to the single customer.Keywords: experiential marketing, social environment, marital status